Knowledge, attitude, and behaviour of physical education and sports students’ about dietary supplements: Dietary supplement use of sports students - Tevfikoglu Pehlivan, Leyla; Ateş Özcan, Burcu; Erem, Sinem; Ercan, Aydan; Akkaya, İzel; Başarır, Aylin (Progress in Nutrition, 2020)
Study Objectives: This study was carried out to determine the knowledge, attitude, and behavior of sports students’ about dietary supplements. Method: This study was carried out voluntarily by applying face-to-face questionnaires with 145 students aged 18-25, 37.9% female, and 62.1% male, studying at Trakya University School of Physical Education and Sports. The questionnaire includes demographic information of the participants, information and use of dietary supplements, and anthropometric measurements. Results: 45.5% of the students used dietary support, and the rate of dietary support usage of males (30.3%) was higher than dietary support usage of females (15.2%) (p>0.05). It was found that 11.7% of the students received information from doctors / dieticians, 13.8% from trainers, and 18.6% from other sources (internet, television, friends) (p